Limping legislation – viability of the Indian Nuclear Liability Act within the constitutional scheme. (6th August 2012) - Mohanty, Tanavi; Kumar, Aayush
India's launch into the international nuclear regime has been controversial with allegations of being unconstitutional being levied on its liability legislation, the Civil Liability Act. This paper proposes to argue the legality of the legislation on the parameters of Constitutional mandates in fundamental rights of life, liberty and equality. On dissection, it finds the legislation in breach of environmental principles recognised in both national and international legal regimes. The Act is hit by arbitrariness of state action in many of its provisions. Finally, the eviction of Courts from the compensatory mechanism rounds up the attack. The gravity of the issue has been examined in the matrix of imminent dangers of dealing with nuclear energy. In its last limb, the paper proposes a correction of the Act to put the law onto an effective road to implementation and suggests ways to put it into action.